Synthesis and Characterization of as-formed and Calcined MnFe2O4 nanoparticles: A comparative study of their Antibacterial Activities. (2017) - Ashwini, K.; Rajanaika, H.; Anantharaju, K.S.; Nagabhushanad, H.; Adinarayana Reddy, P.; Shetty, Krushitha; Vishnu Mahesh, K.R.
Abstract: In this study, MnFe2 O4 NPs were synthesized through Solution combustion method at a temperature of about 450°C using Oxalyl Dihydrazide (ODH) as a chemical fuel. The synthesized MnFe2 O4 nanomaterial was calcined at a temperature of 700°C. The structural properties and surface morphology of the synthesized NPs were characterized by Powder X-ray Diffraction technique (PXRD) and Scanning Electron Microscopy (SEM). Further these NPs were subjected to antibacterial studies with different strains of Gram-positive and Gram-negative bacteria by Agar well diffusion method and Microbroth dilution technique. The comparison between the bacterial inhibition potential of the synthesized NPs were investigated by the zone of inhibition obtained around the agar wells and the colour change obtained in the titre plate wells containing the bacterial suspension with respect to different concentrations of the as-formed and calcined MnFe2 O4 NPs.